Indonesian Version of DREEM Short Form Construct Validity Test in Measuring Student Perception of Distance Learning Environment - Aviva Lutfiana; Rose Mini Agoes Salim (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
English: The learning environment is very important to support student achievement. During the COVID-19 pandemic until the new normal transition, students are faced with a changing learning environment, starting from online, hybrid, to full offline. Dundee Ready Education Environment Measure (DREEM) is an instrument that measures students' perceptions of their learning environment in medical institutions developed by Roff, et.al. (1997). DREEM initially consist of 50-item to measure five domains, it was later developed into a 12-item short version by Jeyashree, Shewade, and Kathrivel (2018). There is no adapted version of DREEM short-form for non-medical institutions in Indonesia. Therefore, this study aims to adapt and validate the DREEM short-form measurement tool for a wider range of institutions. The population of this instrument testing are students in Indonesia with a sample of 160 people. The results show that the instrument has good internal consistency (α= 0.896), able to distinguish individuals in groups based on discrimination items, and valid in measuring constructs (Model Fit CFI = 0.922; GFI = 0.901; SRMR = 0.055, and have a good factor loading). Thus, Indonesian version of DREEM short-form is a valid and reliable tool for use in research in the field of education in a wider range of institutions.Indonesian: Lingkungan pembelajaran sangatlah penting untuk mendukung prestasi mahasiswa. Pada masa pandemi COVID-19 hingga transisi new normal, mahasiswa dihadapkan dengan lingkungan pembelajaran yang berubah-ubah, dimulai dari daring, hybrid, hingga full luring. Dundee Ready Education Environment Measure (DREEM) merupakan instrumen yang mengukur persepsi mahasiswa terhadap lingkungan pembelajarannya dalam institusi medis yang dikembangkan oleh Roff, et.al. (1997). Awalnya DREEM berjumlah 50-item untuk mengukur lima domain, kemudian dikembangkan dalam versi singkat (short-form) 12-item oleh Jeyashree, Shewade, dan Kathrivel (2018). Selama ini belum ada alat ukur dalam Bahasa Indonesia untuk DREEM short version 12-item untuk institusi di luar medis. Maka penelitian ini bertujuan untuk membuat adaptasi dan validasi alat ukur DREEM Short-Form 12-item untuk institusi yang lebih luas. Populasi dari pengujian alat ukur ini adalah mahasiswa di Indonesia dengan sampel sebanyak 160 orang. Hasilnya menunjukkan bahwa alat ukur yang telah diadaptasi memiliki konsistensi internal yang baik (reliabilitas α= 0.896), mampu membedakan individu dalam kelompok berdasarkan item discrimination, dan valid dalam mengukur konstruk (Model Fit CFI = 0,922; GFI = 0,901; SRMR = 0,055, dan memiliki muatan faktor yang baik). Dengan begitu, DREEM-12 Bahasa Indonesia merupakan alat ukur yang valid dan reliabel untuk digunakan dalam penelitian di bidang pendidikan pada setting yang lebih luas.